Strategi Komunikasi Pemasaran “Connection 88 Cafe Medan” Menggunakan Instagram dalam Meningkatkan Jumlah Konsumen - Rizki Ermaliza; Endang Sulistya Rini; Fadli Fadli (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to describe the marketing communication strategy through Instagram implemented by Connection 88 Café Medan. The background of this study is a decrease in the number of visitors which is suspected to be caused by a marketing strategy that is not optimal. Problems found include a lack of interaction with consumers on Instagram, such as rarely reposting customer Insta Stories, an unattractive feed display, inconsistency in uploading content every day, and not using influencer marketing as a promotional tool. This study uses a qualitative method with a descriptive approach. Informants in this study numbered fifteen people, consisting of one owner, one manager, and thirteen consumers of Connection 88 Café Medan. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out inductively to gain a deep understanding of the marketing communication strategy implemented. The results of the study indicate that the use of Instagram as a marketing medium is considered quite effective because it is able to increase brand awareness, expand the reach of information, and encourage an increase in the number of consumers visiting Connection 88 Café Medan in a sustainable manner and support the achievement of culinary business marketing goals.